Water vapor–assisted carbonation of steel slag: calcium source contributions and kinetic behavior - Yuedong Wu; Haitao Wang; Meng Han; Yining Kang; Ben Peng; Longheng Xiao (Journal of Environmental Management, 2026)

Retraction notice to “Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period” [Sci. Total Environ. 906 (2024) 167622] - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2026)

Corrigendum to “Sodium cyclamate enhances Vibrio parahaemolyticus biofilm formation on seafood-contact surfaces” [Food Res. Int. 235 (2026) 119195] - Yining Zhou; Nan Zhang; Wu Xu; Xue Li; Miaomiao Zhang; Xi Luo; Bin Ni; Feng Huang; Renfei Lu; Yiquan Zhang; Xudong Han (Food Research International, 2026)

Sodium cyclamate enhances Vibrio parahaemolyticus biofilm formation on seafood-contact surfaces - Yining Zhou; Nan Zhang; Wu Xu; Xue Li; Miaomiao Zhang; Xi Luo; Bin Ni; Feng Huang; Renfei Lu; Yiquan Zhang; Xudong Han (Food Research International, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

A visual method for identifying local over-densities in spatial data - Yining Han; Xiaobin Chen; Xingxing Huang; Zhongyin Liu (Spatial Statistics, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Flexible metal-organic frameworks with dual-state emitters (DSEs) Photoluminescence for portable detection and information encryption - Qiao Han; Qingbo An; Xiao Li; Jiaxing Chang; Si Liu; Yining Wang; Zhong-min Su (Analytica Chimica Acta, 2025)

Ultra-durable ZIF-7 superhydrophobic coating for long-term corrosion protection in aircraft nacelles lips - Ritong Wang; Zuozhu Yin; Xiangyu Han; Yining Zhang; Suhang Zhang; Xiangyu Lan; Yuhua Chen; Zhen Hong; Chan Xie; Jilin Xu; Mingshan Xue (Chemical Engineering Journal, 2025)

A Nonspherical Cloud Scattering Database Using Aggregates of Roughened Bullet Rosettes Model for the Advanced Radiative Transfer Modeling System (ARMS) - Ziyue Huang; Hanyu Lu; Ziqiang Ma; Yining Shi; Yang Han; Hao Hu; Jun Yang (Advances in Atmospheric Sciences, 2025)

Field-road trajectory classification for agricultural machinery by integrating spatio-temporal clustering and semantic segmentation - Yining Han; Zhiqing Huang; Pei Xu (Computers and Electronics in Agriculture, 2025)

Estimation of volumetric block proportions from 1D boring of bim-materials considering different block forms - Han Zhang; Chengyou Huang; Lehua Wang; Yining Cao; Daniela Boldini (Engineering Geology, 2025)

Landscapes of alternative splicing genes/events in the gills of Mozambique tilapia (Oreochromis mossambicus) and their roles in high-salinity adaptation - Ming Huang; Han Yu; Boyuan Wang; Wenxin Jiang; Na Xue; Hancheng Bao; Yining Yu; Qingkai Tang; Qinfeng Gao; Yuan Tian (Aquaculture International, 2025)

Towards a point cloud understanding framework for forest scene semantic segmentation across forest types and sensor platforms - Hao Lu; Bowen Li; Gang Yang; Guangpeng Fan; Han Wang; Yong Pang; Zuyuan Wang; Yining Lian; Haifeng Xu; Huan Huang (Remote Sensing of Environment, 2025)

Delayed response of the coastal sedimentary record to the southward shift of the Huanghe (Yellow River) course during AD1128–1855 - Chengfeng Xue; Yang Yang; Xibin Han; Ya Ping Wang; Yining Chen; Xiaoming Xia; Jianjun Jia (Marine Geology, 2025)

Serum levels of perchlorate and chlorate in pregnant women from south China and the related health risk with thyroid function - Yining Chen; Han Zhang; Shaoyou Lu; Yiming Ge; Jiajia Ji; Tao Chen (Food and Chemical Toxicology, 2024)

Perchlorate in foodstuffs from South China and its implication for human dietary exposure - Yining Chen; Han Zhang; Yiming Ge; Zhou Zhu; Jiajia Ji; Donghui Luo; Shaoyou Lu (Food and Chemical Toxicology, 2024)

Effect of salt-tolerant rice (Oryza sativa L.) cultivation on soil bacterial community and ecological function groups in coastal saline land - Xuefeng Xie; Ruotong Ji; Ziqing Xu; Qi Shao; Lijie Pu; Zhenyi Jia; Tao Wu; Fei Xu; Jian Hu; Yuanqin Miu; Lingyue Zhu; Zaiyang Tian; et al. (Applied Soil Ecology, 2024)

Enhanced Target Localization in the Internet of Underwater Things through Quantum-Behaved Metaheuristic Optimization with Multi-Strategy Integration - Xiaojun Mei; Fahui Miao; Weijun Wang; Huafeng Wu; Bing Han; Zhongdai Wu; Xinqiang Chen; Jiangfeng Xian; Yuanyuan Zhang; Yining Zang (Journal of Marine Science and Engineering, 2024)
Underwater localization is considered a critical technique in the Internet of Underwater Things (IoUTs). However, acquiring accurate location information is challenging due to the heterogeneous underwater environment and the hostile propagation of acoustic signals, especially when using received signal strength (RSS)-based techniques. Additionally, most current solutions rely on strict mathematical expressions, which limits their effectiveness in certain scenarios. To address these challenges, this study develops a quantum-behaved meta-heuristic algorithm, called quantum enhanced Harris hawks optimization (QEHHO), to solve the localization problem without requiring strict mathematical assumptions. The algorithm builds on the original Harris hawks optimization (HHO) by integrating four strategies into various phases to avoid local minima. The initiation phase incorporates good point set theory and quantum computing to enhance the population quality, while a random nonlinear technique is introduced in the transition phase to expand the exploration region in the early stages. A correction mechanism and exploration enhancement combining the slime mold algorithm (SMA) and quasi-oppositional learning (QOL) are further developed to find an optimal solution. Furthermore, the RSS-based Cramér–Raolower bound (CRLB) is derived to evaluate the effectiveness of QEHHO. Simulation results demonstrate the superior performance of QEHHO under various conditions compared to other state-of-the-art closed-form-expression- and meta-heuristic-based solutions.

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Metabolic engineering of Schizochytrium sp. for superior docosahexaenoic acid production - Xiao Han; Yana Liu; Yining Yuan; Zhi Chen (Algal Research, 2024)

Reaction mechanism of selective catalytic reduction of NO with NH3 on Fe3O4 (1 1 1) surface: Experimental and DFT studies - Guozhen Qin; Yining Zhang; Jianfeng Zheng; Yifan Li; Xiaojin Han; Zhanggen Huang (Fuel, 2023)

Production and identification of dipeptidyl peptidase IV (DPP-IV) inhibitory peptides from discarded cowhide collagen - Long He; Xinyue Wang; Yanru Wang; Jin Luo; Yining Zhao; Guangxing Han; Ling Han; Qunli Yu (Food Chemistry, 2023)

Two complete mitochondrial genomes in Scolopendra and a comparative analysis of tRNA rearrangements in centipedes - Jiayu Ding; Hong Lan; Wei Xu; Yining Chen; Han Wu; Haoming Jiang; Jiachen Wang; Yongbo Wu; Hongyi Liu (Molecular Biology Reports, 2022)